Teaching Speaking with the Communicative Approach in a Bilingual Junior High School: Strategies and Challenges - Muhammad, Ilhamuddin; Basori, Basori (English Edu: Journal of English Teaching and Learning, 2024)
English is one of the languages used as a lingua franca by the majority of the world’s citizens. One of the essential abilities of mastering a language is the ability to speak, so the ability to speak English is increasingly needed. The communicative approach is based on the idea that communicating or speaking with real meaning is necessary for successful language learning. This study aims to: (1) find what are the strategies that teachers used to implement a communicative approach in teaching speaking, and (2) how teachers face challenges in the classroom when teaching English speaking using a communicative approach at the junior high school educational level. This study uses a qualitative case study and using observation and semi-structured interviews with six English teachers the data were gathered. The findings show that: (1) From teachers observed and interviewed, a few teaching strategies that can be applied to carry out the communicative approach such as Telling a Story, Listen and Repeat, Short Conversation & Guided Speaking, and Group Discussion & Presentation. (2) Each teacher encounters different challenges from the strategies they apply to carry out a communicative approach in teaching speaking such as passive student issues, understanding student’s sentence structure, the teacher’s voice running out, and lack of motivation and enthusiasm. This research is limited to one junior high school that has English teachers to study. For future research, it can use more subjects and has a wider scope with various educational institutions, especially at the junior high school educational level. The data can be collected using closed-ended questions to make it easier to collect data from subjects and filter data.